Teaching death and dying - Moreman, Christopher M. (Teaching religious studies series, 2008)
Section 1: What ought a course on death accomplish? -- What should a course on death and dying accomplish? : death education in an undergraduate religion course / Lucy Bregman -- Ethical issues in teaching death and dying : pedagogical aims in end-of-life ethics / Christian Perring -- Section 4: Practical applications of a course on death -- Teaching death and dying : a pastoral theological approach / G. Lee Ramsey -- Death, loss, and bereavement : the role of social work / Estelle Hopmeyer -- Psychology, grief, and the student / David E. Balk -- Section 3: Media as teacher and aid to teaching -- The virtual resurrection : technology, violence, and interpretations of death in a southern university classroom / Diana Walsh Pasulka -- What would Spielberg do? : using mainstream films to teach visions of the afterlife / Michael McKenzie -- Section 4: Death in context -- Death and dying in history / Albert N. Hamscher -- Teaching outside the classroom : the use of site visits / Kathleen Garces-Foley -- Section 5: Literatures of death and on death -- Literature, textbook, and primary source : constructing the reading list / Sarah Pinnock -- Listen to the dark : death and dying in music, film, and literature / Amir Hussain -- Love letters to the dead : immortal gifts for the lifelong learner / Dorothy Lander and John Graham-Pole -- Section 6: Course overviews -- How death and dying can act as an introduction to world religion / Vanessa R. Sasson -- Death, dying, and transcendence / Brenda Appleby -- Section 7: Life after death -- Life after death : an overview of contemporary beliefs for teachers / Paul Badham -- Why an investigation of paranormal experience should be an essential component of a course on death / L. Stafford Betty